Structural maturation of the HIV-1 RNA 5' untranslated region by Pr55Gag and its maturation products. Issue 1 (31st December 2022) - Gilmer, Orian; Mailler, Elodie; Paillart, Jean-Christophe; Mouhand, Assia; Tisné, Carine; Mak, Johnson; Smyth, Redmond P.; Marquet, Roland; Vivet-Boudou, Valérie
ABSTRACT: Maturation of the HIV-1 viral particles shortly after budding is required for infectivity. During this process, the Pr55 Gag precursor undergoes a cascade of proteolytic cleavages, and whilst the structural rearrangements of the viral proteins are well understood, the concomitant maturation of the genomic RNA (gRNA) structure is unexplored, despite evidence that it is required for infectivity. To get insight into this process, we systematically analysed the interactions between Pr55 Gag or its maturation products (NCp15, NCp9 and NCp7) and the 5ʹ gRNA region and their structural consequences, in vitro . We show that Pr55 Gag and its maturation products mostly bind at different RNA sites and with different contributions of their two zinc knuckle domains. Importantly, these proteins have different transient and permanent effects on the RNA structure, the late NCp9 and NCp7 inducing dramatic structural rearrangements. Altogether, our results reveal the distinct contributions of the different Pr55 Gag maturation products on the gRNA structural maturation.